The Effect Of Massage Effleurage On Pain Intensity And Length Of Labor I In The Normal Inpartu In Tuban District - Qonitun, Umu (Jurnal Midpro, 2020)
The labor process is characterized by a physiological pain that is pain that occurs when the muscles contract in an effort to open the cervix and push the baby's head towards the pelvis. Effleurage is a slow massage of the abdomen or other body parts during contractions, warm compresses are actions to meet the needs of a sense of comfort, reduce pain.The method used is experimental analytic with pre-experimental design (Static-group comparation design). The population of all normal delivery mothers in the first active phase in the Delima Midwife in the District of Tuban was 46 people, a large sample of 18 respondents using systematic random sampling. Data collection instrument comparative pain scale observation sheet. Analysis of research using the t-Test (Independent t-Test).Statistical test results show the effect of massage effleurage on the intensity of first stage active labor pain in normal delivery mothers in Delima Midwives in Jadi Village, Tuban District with p value massage effleurage 0.03 while the effect of massage effleurage on the duration of first stage active labor in normal birth mothers in normal birth mothers Delima Village Midwife Becomes Tuban District with a p value of 0.04.Based on the results show that massage effleurage can be used as a method in dealing with labor pain in the first phase of active phase so that the delivery process becomes more comfortable, for this research it can be used as an additional reference for health workers, educational institutions and further researchers to deliver labor to the public.